Rancangan Desain Sump pada Pit Jamrud Kabupaten Konawe Utara Sulawesi Tenggara - Ika Sartika Ambarsari; Deniyatno; Erwin Anshari; Arif Setiawan (Universitas Halu Oleo, 2024)
A sump is a drainage facility located at the bottom of the pit. The sump design must be appropriate so that runoff water flowing on the surface can be maximally accommodated. This can overcome stagnant water on the ground and avoid disruptions to mining productivity. Jamrud Pit has an area of 4.14 ha and is mined using the open pit method. The purpose of this research is to calculate and analyze the water discharge that will enter the sump and design the sump according to the volume of runoff water entering the sump. Based on the research results, there are two sumps placed at the bottom of the pit according to the pit cross-section model. Sump 1 has a runoff water volume of 2,914.24 m3, so it is designed with a top area of 27 x 27 m2 and a base area of 21 x 21 m2 with a depth of 5 m and can accommodate a water volume of 2,997.6 m3. While in sump 2, the volume of incoming runoff water is 579.85 m3, so it is designed with a top area of 14 x 14 m2 and a base area of 8 x 8 m2 with a depth of 5 m so that it can accommodate a water volume of 663.18 m3. The sump cross-section model is adjusted to the characteristics of the soil layer, namely the trapezoidal model.